Hole states in fluorine-doped La2CuO4 thin films probed by polarized x-ray-absorption spectroscopy - Chen, J; Nachimuthu, P; Liu, R; Lees, S; Gibbons, K; Gameson, I; Jones, M; Edwards, P (1999)
High-resolution polarized x-ray-absorption spectra at the O K edge and Cu L edge for c-axis-oriented La2CuO4Fx thin films using a bulk-sensitive x-ray-fluorescence-yield detection method were investigated. In the O 1s absorption edge of La2CuO4Fx, the prepeak at 528.7 eV is assigned to transitions into O 2pxy hole states located in the CuO2 planes. Fluoride ions present in La2CuO4Fx induce hole states in the CuO2 planes near the Fermi level, which in turn play an important role in enhancing superconductivity for this compound, as compared to parent La2CuO4. Thus, in La2CuO4Fx, fluoride ions are regarded as an electronic dopant to induce superconductivity. ©1999 The American Physical Society.